PENGEMBANGAN MEDIA PEMBELAJARAN PHYSICS MAGZ TERINTEGRASI AL-QUR'AN TERHADAP PENINGKATAN HASIL BELAJAR PESERTA DIDIK - Wahyuni, Sri; Fatmi, Nuraini; Faradhillah, Faradhillah; Ginting, Fajrul Wahdi; Setiawan, Tulus (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2023)
One of the characteristics of the 2013 curriculum is balancing the spiritual abilities of students. In the 2013 curriculum there are four core competencies as standard benchmarks for the success of the learning process. The spiritual aspect in the K-13 curriculum is placed as the first aspect in core competencies. This shows that the spiritual aspect is very important to pay attention to. Therefore, the integration of spiritual attitudes really needs to be conveyed by the teacher. Teachers are required to be more creative in planning and implementing learning so that spiritual balancing and Islamic values ​​are well represented in the learning process. This can be realized one way by integrating the verses of the Qur'an into learning media. Based on the results of interviews at MTsN 9 Bireuen, it shows that there is no physics learning media integrated with the Qur'an. This study aims to develop magazine learning media that are valid, practical and can improve student learning outcomes. This research is R&D with the ADDIE model. The results showed that the validity level of the magazine was in the very valid category, practicality with the very practical category, while for improving the cognitive learning outcomes of students in the experimental class, the results of the N-Gain test were obtained with a value of 0.57 in the